Microwell-based pancreas-on-chip model enhances genes expression and functionality of rat islets of Langerhans. (20th August 2020) - Essaouiba, Amal; Okitsu, Teru; Jellali, Rachid; Shinohara, Marie; Danoy, Mathieu; Tauran, Yannick; Legallais, Cécile; Sakai, Yasuyuki; Leclerc, Eric
Abstract: Organ-on-chip technology is a promising tool for investigating physiological in vitro responses in drug screening development, and in advanced disease models. Within this framework, we investigated the behavior of rat islets of Langerhans in an organ-on-chip model. The islets were trapped by sedimentation in a biochip with a microstructure based on microwells, and perfused for 5 days of culture. The live/dead assay confirmed the high viability of the islets in the biochip cultures. The microfluidic culture leads to upregulation of mRNA levels of important pancreatic islet genes: Ins1, App, Insr, Gcgr, Reg3a and Neurod . Furthermore, insulin and glucagon secretion were higher in the biochips compared to the Petri conditions after 5 days of culture. We also confirmed glucose-induced insulin secretion in biochips via high and low glucose stimulations leading to high/low insulin secretion. The high responsiveness of the pancreatic islets to glucagon-like peptide 1 (GLP-1) stimulation in the biochips was reflected by the upregulation of mRNA levels of Gcgr, Reg3a, Neurog3, Ins1, Ins2, Stt and Glp-1r and by increased insulin secretion. The results obtained highlighted the functionality of the islets in the biochips and illustrated the potential of our pancreas-on-chip model for future pancreatic disease modeling and anti-diabetic drugs screening. Highlights: Rat islets were cultivated in dynamic biochip and compared to Petri cultures. Islets in biochips presented high viability and functionality. Pancreatic islets markers were overexpressed in microfluidic culture. Microfluidic environment enhance insulin and glucagon production. The islets preserved their responsiveness to low/high glucose and GLP-1 stimulation.